PERSEPSI SISWA TERHADAP KINERJA KONSELOR DI SMA NEGERI SE- KOTA SEMARANG TAHUN PELAJARAN 2013/2014 - Kartiko, Ong Didik Cahyo (Indonesian Journal of Guidance and Counseling: Theory and Application, 2014)
The purpose of this study is obtain a general overview of counselor performance and determine the level of studentâs perceptions of the counselors performance. The population in this study were all high school students in Semarang, and a sample of 329 students were taken using proportional random cluster sampling to sample the region, and stratified random sampling to sample a number of students. Methods of data collection using a scale psychological, perception scale. The validity of the instrument using the product moment formula and the calculation of reliability using the alpha formula. Data analysis technique used is descriptive analysis percentage. These results indicate the level of students perception of the counselors performance in the average category (65.65%).